Differential effects of trade on economic growth and investment: A cross-country empirical investigation - Maureen Were (Journal of African Trade, 2015)
The paper empirically examines the differential effects of trade on economic growth and investment based on cross-country data. In general, the results are largely consistent with the positive impact of trade on economic growth as found in the literature. However, the empirical results based on different categories of countries show that whereas trade has positively impacted economic growth in developed and developing countries, its effect is insignificant for least developed countries (LDCs), which largely include African countries. Nonetheless, additional results suggest that trade is a key determinant of foreign direct investment (FDI) across all country groups including LDCs, as well as domestic investment in both developing countries and the LDCs. Consequently, first, the structure and pattern of trade in LDCs and African countries in particular should be transformed in order to obtain larger growth benefits as in the case of the other country groups. Second, trade, particularly via the investment channel, is an avenue through which LDCs, including African countries, can adopt new technologies and attract FDI to unlock their potential, e.g., by active integration into regional and global value chains.
Keywords: F10; F40; F49; F43; 330; Trade; Economic growth; LDCs; Developing countries; FDI